Epidemiological overview of AIDS in elderly people in the state of Santa Catarina from 2008 to 2018 - Miotto, Geovana Elizabeth; Iser, Daniel Albrecht; Iser, Betine Pinto Moehlecke; Ribeiro, Bruno Tafarel; Castilhos, Fernanda Brigido (Brazilian Journal of Sexually Transmitted Diseases, 2021)
Introduction: In recent years there has been an increase in the number of AIDS diagnoses in the general population, with a significant growth among elderly individuals. Objective: To analyze the epidemiological situation of AIDS in the elderly population and its temporal trend in the Santa Catarina State. Methods: Ecological study, conducted with the elderly (≥60 years) living in Santa Catarina, who were diagnosed with AIDS and notified in the Brazilian Information System for Notifiable Diseases (SINAN) from 2008 to 2018. The incidence rate according to sex, age group and health macro‑region was calculated, as well as the time trend, through linear regression. Race/skin color and scholarity were analyzed by proportion in relation to the total. Results: 1,365 cases were notified from 2008 to 2018. There was an increase in cases from 6,7/100.000 in 2008 to 23,1 in 2018 (1,77% yearly), higher among men aged 60 to 69 and living in the area of Florianópolis. Conclusion: there was an increase in AIDS notifications among the elderly in the state.